2017
DOI: 10.3390/polym9120689
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Application of Polysaccharide-Based Metallic Nanoparticles: A Review

Abstract: Abstract:Polysaccharides are natural biopolymers that have been recognized to be the most promising hosts for the synthesis of metallic nanoparticles (MNPs) because of their outstanding biocompatible and biodegradable properties. Polysaccharides are diverse in size and molecular chains, making them suitable for the reduction and stabilization of MNPs. Considerable research has been directed toward investigating polysaccharide-based metallic nanoparticles (PMNPs) through host-guest strategy. In this review, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(42 citation statements)
references
References 235 publications
0
42
0
Order By: Relevance
“…Many plants [11,12,21,[24][25][26], algae [4], microorganisms [1,3,[7][8][9][10]14,18,23,[27][28][29][30], as well as redox-imbalanced mammalian cells and systems [31] are known to produce nanostructured mineral crystals and metallic NPs with properties similar to chemically-synthesized materials. Biological agents, including polysaccharides, polypeptides, DNA, enzymes secreted by cells [24,[32][33][34][35][36][37][38][39][40][41] and purified enzymes [42,43] are able to reduce noble metal ions to gain metallic NPs. Besides the practical aim of gNPs production, investigations on the green synthesis processes will be useful for elucidating the mechanisms of cells' responses to stress caused by metal ions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many plants [11,12,21,[24][25][26], algae [4], microorganisms [1,3,[7][8][9][10]14,18,23,[27][28][29][30], as well as redox-imbalanced mammalian cells and systems [31] are known to produce nanostructured mineral crystals and metallic NPs with properties similar to chemically-synthesized materials. Biological agents, including polysaccharides, polypeptides, DNA, enzymes secreted by cells [24,[32][33][34][35][36][37][38][39][40][41] and purified enzymes [42,43] are able to reduce noble metal ions to gain metallic NPs. Besides the practical aim of gNPs production, investigations on the green synthesis processes will be useful for elucidating the mechanisms of cells' responses to stress caused by metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) can afford information on the size, distribution and shape of the gNPs. However, the drying and contrasting processes alter the characteristics of the tested NPs and lead to imaging faults or artifacts [32]. Transmission electron microscopy (TEM) is a high-tech approach in the characterization of gNPs, and is more powerful and competitive than SEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharides are regarded to be polymers with low toxicity exerting few side effects if applied in vivo [32]. In our study, we found that water-soluble polysaccharide from the A. heterophyllus exerted very low toxic effects on the viability and metabolic activity of human colon carcinoma cells.…”
Section: Discussionmentioning
confidence: 60%
“…In this review, we report various possibilities for improving the topographical, mechanical and cell-adhesive properties of aliphatic polyester nanofibers via an electrospinning process [13]. The next two articles discuss the synthesis and characterization of novel inclusion complexes between amylose and polymers, and polysaccharides and metal ions [14,15]. Unlike most of the articles reported in this Special Issue, which are based on CDs, complexation with polysaccharides is unique and hard to accomplish; this review provides a useful starting resource for further research.…”
mentioning
confidence: 99%